2021
DOI: 10.11604/pamj.2021.39.10.27813
|View full text |Cite
|
Sign up to set email alerts
|

Performance de l´imagerie par résonnance magnétique dans l´approche histopathologique des tumeurs parotidiennes

Abstract: Introduction la glande parotide est le siège préférentiel des tumeurs des glandes salivaires. Ces tumeurs sont rares mais se distinguent par une grande diversité histologique, posant ainsi des difficultés diagnostiques. L´imagerie par résonance magnétique (IRM) constitue actuellement le moyen d´imagerie le plus fiable dans l´exploration de ces tumeurs. Le but de notre étude était de préciser la valeur diagnostique de l'IRM et son rôle dans l'approche histopathologique de ces tumeurs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Some authors suggest the combination of cytology and MRI (ref. 28,29 ). However, the availability of MRI in a reasonable time frame for all patients with parotid gland mass may pose difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest the combination of cytology and MRI (ref. 28,29 ). However, the availability of MRI in a reasonable time frame for all patients with parotid gland mass may pose difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Lloyd et al [17] found in a sample of 246 patients with sinonasal tumour (98% of cases). A possible explanation of these variations in sensitivity and specificity rates could be the existence of indeterminate or atypical pathology specimens that were variably considered as benign or malignant by various authors [18]. Nevertheless, CT scan seems to strongly correlate with histology of sinonasal tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The features of MRI sequences are critical in the diagnosis of parotid neoplasms. 27 , 28 , 29 , 30 The present study is innovative in terms of utilizing a newly designed CNN to classify parotid gland tumors. Briefly, the first two layers of the pre‐trained Resnet‐18 were selected to extract the overall image features based on the concept of learning transfer.…”
Section: Discussionmentioning
confidence: 99%